Effects of intellectual disability and attachment on hostile intent attribution bias. Issue 6 (2nd November 2022) - Vanwalleghem, Stéphanie; Miljkovitch, Raphaële; Vinter, Annie
ABSTRACT: Understanding hostile intent attribution (HIA) seems important for prevention of problems in social adaptation. This study aimed to explore whether HIA in childhood is determined by both a cognitive factor (i.e. intellectual disability) and an affective factor (i.e. attachment representations). One hundred and eight 8- to 12-year-old children (54 with intellectual disability and 54 with typical development) passed the Attachment Story Completion Task and the Intention Attribution Test for Children. Results indicated that in ambiguous situations, attachment disorganization was associated with HIA, whereas intellectual disability was not. In nonintentional situations, both attachment hyperactivation and intellectual disability were linked with HIA. These results highlight the importance of helping children develop organized attachment representations and optimal activation of their attachment system to prevent social maladaptation.